Budaya Perkawinan dalam Bentuk Pemaksaan Perkawinan Vs Tindak Pidana dalam Lingkup Perkawinan Menurut Perspektif Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Ery Kurnia; Albar Aliyyus (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Marriage in Indonesia's indigenous peoples has strong cultural values and has been passed down from generation to generation. However, in practice, there are several forms of customary marriage that have the potential to contradict the applicable positive law, especially related to coercive actions in marriage. This study aims to identify and analyze the implementation of marriage culture in the form of forced marriage/captive marriage which is contrary to Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law) that occurs in Sumba, East Nusa Tenggara. This study uses a descriptive qualitative method with a normative juridical approach, this study explores the content of the articles of the Marriage Law, the Criminal Code, and the TPKS Law. In the Indonesian legal system, marriage must meet the elements in the laws and regulations. However, in practice, the traditional marriage culture in Sumba has the potential to lead to forced marriage carried out by men where women are in a vulnerable position. Article 4 paragraph (1) of the TPKS Law clearly states that forced marriage is a form of sexual violence, which can be subject to criminal sanctions in accordance with Article 10 of the TPKS Law. Based on the results of the research, the cultural implications or impacts of forced marriage are the lack of justice, usefulness and legal certainty, so concrete steps are needed in the form of firmer law enforcement and the need for collaborative support from law enforcement officials and legal education for indigenous peoples so that these practices can be minimized and women's rights in marriage can be optimally protected.